2023
DOI: 10.3390/app13106347
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal Model Study of Seepage and Seismic Behavior in a Homogeneous Reservoir Dam with Parapet

Abstract: This study examines the effectiveness of parapets in preventing overtopping failures of small-scale homogeneous reservoir dams under seismic loads. In this study, a parapet covered the entire width of the dam crest and was designed to ensure its weight is transmitted to the dam crest. The test included four modes: initial mode, first seepage, seismic, and second seepage. The results show that without parapets the crack length and width expand significantly in the dam crest during the seismic mode, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In contrast, when anticipating an increase in water level due to heavy rainfall, it is crucial to consider the potential for water leakage at the boundary between the structure and the dam crest in terms of overtopping height and resistance. Previous research findings on the parapet model, specifically designed for preventing dam overtopping, indicate that the design is restricted to a range of 0.5-1 m owing to the risk of water leakage at the dam crest interface [10].…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, when anticipating an increase in water level due to heavy rainfall, it is crucial to consider the potential for water leakage at the boundary between the structure and the dam crest in terms of overtopping height and resistance. Previous research findings on the parapet model, specifically designed for preventing dam overtopping, indicate that the design is restricted to a range of 0.5-1 m owing to the risk of water leakage at the dam crest interface [10].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…The historical context, including the agricultural infrastructure focus of the Japanese colonial period and the Korean War, promoted the economical and rapid construction of earthen dams [9]. Most of these dams were constructed to low design standards in the 1900s, without considering their service life [10]. In 2020, 22 reservoirs failed during the rainy season, and the primary failure factor was age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last several decades, dam slope stability has been studied using a centrifuge, an approach that revealed the mechanism of dam slope failure with water level fluctuations [34][35][36]. It was found that fluctuations in reservoir water levels lead to changes in the PWP and the matric suction in the dam body, reducing the effective stress there; this is unfavorable to the Fs of the dam slope [37]. With the help of modern data transmission technology, dam slopes have been widely studied using field monitoring, which has yielded many useful results [38,39].…”
Section: Introductionmentioning
confidence: 99%